2018
DOI: 10.31334/trans.v9i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengetahuan Pajak, Pengetahuan Zakat Dan Sikap Terhadap Kepatuhan Wajib Pajak Muslim

Abstract: Abstrak. Sinergi peraturan perpajakan dan zakat yang tercantum dalam undang-undang Republik Indonesia nomor 38 tahun 1999 tentang pengelolaan zakat dan nomor 17 tahun 2000 tentang pajak penghasilan, dapat dilihat sebagai langkah maju dalam integrasi pajak dan zakat. Pengetahuan para wajib pajak Muslim tentang adanya sinergi ini penting untuk menumbuhkan perilaku yang obyektif yang dapat mempengaruhi sikap wajib pajak dalam menerapkan kepatuhan pajak dengan cara membuat zakat sebagai pengurang penghasilan kena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Lesmana, Panjaitan, and Maimunah (2017) also concluded that in terms of tax compliance, the variables that affecting positively the intention to pay were the control behavioral and moral obligation, while the attitude and subjective norms did not influence it. Yusuf and Ismail (2017) also proved that there was a significant impact of knowledge in taxation and zakat on taxpayers' compliance in paying tax. Saad and Haniffa (2014) found that intention was significant predictor for zakat compliance behavior.…”
Section: Introductionmentioning
confidence: 88%
“…Lesmana, Panjaitan, and Maimunah (2017) also concluded that in terms of tax compliance, the variables that affecting positively the intention to pay were the control behavioral and moral obligation, while the attitude and subjective norms did not influence it. Yusuf and Ismail (2017) also proved that there was a significant impact of knowledge in taxation and zakat on taxpayers' compliance in paying tax. Saad and Haniffa (2014) found that intention was significant predictor for zakat compliance behavior.…”
Section: Introductionmentioning
confidence: 88%
“…It is common knowledge that paying zakat is an obligation for every Muslim. Therefore, Muslims need to have knowledge about zakat [6]. The implementation of zakat still encounters obstacles because the awareness of the Muslim community in the performance of zakat is still not followed by an adequate level of knowledge about zakat [6].…”
Section: Knowledgementioning
confidence: 99%
“…Therefore, Muslims need to have knowledge about zakat [6]. The implementation of zakat still encounters obstacles because the awareness of the Muslim community in the performance of zakat is still not followed by an adequate level of knowledge about zakat [6]. Lack of knowledge about the obligatory zakat types and the mechanism for paying zakat by Islamic law affects zakat payments made by the Muslim community.…”
Section: Knowledgementioning
confidence: 99%
“…Subjek zakat adalah orang Islam yang telah memenuhi nishab atas harta yang dimiliki dengan persyaratan seperti Muslim sudah baligh, merdeka dan berakal (tidak gila), milik yang sempurna (legal secara hukum), serta cukup nishabnya. Sedangkan, objek zakat merupakan kekayaan atau penghasilan yang diperoleh kaum muslimin yang sudah mencapai nishabnya, sehingga kaum muslimin tersebut berkewajiban mengeluarkan sebagaian dari harta yang dimiliki dan diberikannya kepada orang yang berhak menerimanya sesuai dengan syariat Islam (Yusuf & Ismail, 2017).…”
Section: Pendahuluanunclassified
“…Pajak dan zakat tidak dikenakan oleh semua masyarakat Indonesia. Zakat dikenakan atas muslimin yang memiliki kekayaan atau penghasilan yang sudah mencapai nishabnya (Yusuf & Ismail, 2017). Sedangkan, pajak dikenakan atas orang yang penghasilannya melebihi penghasilan tidak kena pajak.…”
Section: Pendahuluanunclassified